Entrepreneurship education in tourism and hospitality management - Bagri, S. C.; Dhodi, Rakesh Kumar, 1971-; Junaid, K. C., 1992- (Advances in hospitality, tourism, and the services industry book series., 2022)
"This focus of this book is to highlight various cases of entrepreneurship education in tourism and hospitality across the World and to discuss and analyze the utility of tourism and hospitality entrepreneurship education due to the new digital revolution and global pandemic"--